2001
DOI: 10.1046/j.0021-8901.2001.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of fishery by‐catches on albatross populations

Abstract: Summary1. Several albatross species, including the wandering albatross Diomedea exulans , have shown marked declines in abundance throughout their range. These seabirds are frequently taken as by-catch in longline fisheries and this mortality has been implicated in the population declines. 2. We developed a deterministic, density-dependent, age-structured model for assessing the effects of longlining on wandering albatross populations. We used demographic data from field studies at South Georgia and the Crozet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
120
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 23 publications
(79 reference statements)
2
120
1
Order By: Relevance
“…Better documented are the direct interactions between seabirds and fisheries, and more particularly bycatch, which may have been implicated in population declines of several species of seabirds in the Southern Ocean (e.g. Weimerskirch et al 1997, Tuck et al 2001. However, the effect of bycatch on demographic parameters and population dynamics remains poorly known for several populations, and even less is known about the potential interactions between bycatch and climate on seabird population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Better documented are the direct interactions between seabirds and fisheries, and more particularly bycatch, which may have been implicated in population declines of several species of seabirds in the Southern Ocean (e.g. Weimerskirch et al 1997, Tuck et al 2001. However, the effect of bycatch on demographic parameters and population dynamics remains poorly known for several populations, and even less is known about the potential interactions between bycatch and climate on seabird population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…At-sea mortality induced by industrial fishing has been identified as the main factor currently affecting seabird populations worldwide (Tuck et al 2001, Lewison et al 2012. In this context, conservation efforts in fishing practice and regulatory meas-ures have been undertaken and/or proposed to mitigate incidental seabird capture at sea (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, quantifying the scale of the problem is difficult due to the diverse and remote nature of many of the world's fisheries, the lack of systematic reporting, and the nature of seabird bycatch rates themselves, which can be highly variable. Nevertheless, several reviews have concluded that recent and/or current reported levels of seabird bycatch are demographically unsustainable for the populations involved (Croxall et al 1998, Tuck et al 2001, Arnold et al 2006, Barbraud et al 2009, Rivalan et al 2010.…”
Section: Introductionmentioning
confidence: 99%